Crystallographic orientation effect on the incipient plasticity and its stochastic behavior of a sapphire single crystal by spherical nanoindentation. Issue 10 (July 2020) - Ma, Yi; Cao, Linlin; Hang, Wei; Zhang, Taihua; Yuan, Julong
Abstract: Relying on spherical nanoindentation, we investigated the characteristics of incipient plasticity via the first pop-in event in the four typical crystallographic orientations of a sapphire single crystal. Statistically, critical loads at the occurrences of incipient plasticity were uniformly distributed in a wide range in A-, C-, and R-planes. While in M-plane, two distinct distribution ranges of the critical loads were discernible. The displacement burst at first pop-in was approximately varied from 5 to 150 nm and strongly dependent on the crystallographic orientation. Cracking and twin deformation were revealed as deformation mechanisms under nanoindentation, whilst their type and size were varied in different orientations. The critical strengths at incipient plasticity and their statistical laws were also summarized. The crystallographic orientation effect on the yielding strength of a sapphire could be well explained from the perspective of deformation mechanisms. The Weibull modulus of stochastic distribution of yield strength was estimated and exhibited higher failure reliability under micro-contact deformation than bulk fracture in sapphire.